2023
DOI: 10.1590/1806-9282.20230076
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum signal peptide-CUB-EGF-like domain-containing protein 1 levels in patients with acute appendicitis

Abstract: SUMMARY OBJECTIVE: Acute appendicitis is one of the most common surgical causes of an acute abdomen among patients admitted to the emergency room due to abdominal pain. The clinical diagnosis of acute appendicitis is usually difficult and is made by evaluating the clinical, laboratory, and radiological findings together. The aim of this study was to investigate the diagnostic potential of signal peptide-CUB-EGF-like domain-containing protein 1 as a biomarker for acute appendicitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…CDCP1, a substrate of Src family kinases, plays a role in regulating resistance to cell death when detached from the extracellular matrix (anoikis), cell migration, and breakdown of the extracellular matrix during the invasion and spread of tumors, speci cally through tyrosine phosphorylation(Uekita & Sakai, 2011). Elevated levels of signal peptide-CUB-EGF-like domain-containing protein 1 (SCUBE1) were observed in adults diagnosed with acute appendicitis, indicating its potential as a novel and promising biomarker for predicting in ammation (Altuntas et al, 2023). In another study (Tokime et al, 2008), neurotrophic factors such as nerve growth factor and GDNF were suggested to be involved in the mechanism underlying the overgrowth and hypersensitivity of sensory nerves in atopic dermatitis (Huang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CDCP1, a substrate of Src family kinases, plays a role in regulating resistance to cell death when detached from the extracellular matrix (anoikis), cell migration, and breakdown of the extracellular matrix during the invasion and spread of tumors, speci cally through tyrosine phosphorylation(Uekita & Sakai, 2011). Elevated levels of signal peptide-CUB-EGF-like domain-containing protein 1 (SCUBE1) were observed in adults diagnosed with acute appendicitis, indicating its potential as a novel and promising biomarker for predicting in ammation (Altuntas et al, 2023). In another study (Tokime et al, 2008), neurotrophic factors such as nerve growth factor and GDNF were suggested to be involved in the mechanism underlying the overgrowth and hypersensitivity of sensory nerves in atopic dermatitis (Huang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%